A reassessment of the role of serotonergic system in the control of feeding behavior - Medeiros,Magda A. (2005)
The role of serotonergic system in the feeding behaviorwas appraised by electrolytic lesions in the dorsal raphe nucleus (DRN) and administration of para-chlorophenylalanine (PCPA, 3 mg/5 mul, icv). Chronic evaluations were accomplished through 120 and 360 days in PCPA-injected and DRN-lesioned rats, respectively. Acute food intake was evaluated in fasted rats and submitted to injection of PCPA and hydroxytryptophan (LHTP, 30 mg/kg, ip). DRN-lesioned rats exhibited 22-80% increase in food intake up to sixth month, whereas the obesity was evident and sustained by whole period. In PCPA-injected rats was observed an initial increase in the food intake followed by hypophagy from 25th to 30th day and a transitory increase of body weight from 5th to 60th day. In the acute study, the LHTP reverted partially the PCPA-induced increase in food intake of fasted rats suggesting a sustained capacity of decarboxylation of precursor by serotonergic neurons. Slow restoration of the levels of food intake in DRN-lesioned rats reveals a neuroplasticity in the systems that regulate feeding behavior. A plateau on the body weight curve in lesioned rats possibly represents the establishment of a new and higher set point of energetic balance.